Educating of young racing sportsmen-motorists to the effective passing of turns on the stage of previous base preparation - Крайник, Л. В.; Ткачек, В. В.; Прийма, С. Б.; Шевчук, А. М. (Physical Education Theory and Methodology, 2012)
Authors picked means and methods of mastering modern effective technique cornerin for young go-kart racers at the initial stage of basic training, which avoids retraining new equipment at the following stages of many athletic improvement. The effectiveness of the developed training program is confirmed with test results: After graduating athletes improved passage of tarmac and gravel competitive areas on the race simulator on average by 7,81% and 4,43% respectively